Factors Influencing Inappropriate Antibiotic Usage Among Patients of Multan Periphery - Shahid Javed, Zaka Ul Rehman, Muhammad Naqash Khan, Muhammad Yosuf, Umair Ahmad, Umair Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the factors that contribute to the inappropriate utilization of antibiotics and to determine their knowledge antimicrobial resistance (AMR). Materials and methods: A total of 280 people who had history of use of antibiotics within last 30 days were included. A questionnaire was build to collect information from respondents (including two separate parts). The first part was including their age, gender socioeconomic status and residential area. The questionnaire also included information to diagnose either the antibiotics use was appropriate or in-appropriate. The 2nd part included information regarding the peron’s knowledge regarding AMR. Results: Among the 280 patients, only 104 (37.1%) patients had appropriate use of antibiotics and remaining 176 (62.9%) had inappropriate use of anti-biotics. patients of age ≤40 years had higher percentage of appropriate antibiotics use; 90 (86.5%) versus 123 (69.9%) using inappropriate antibiotics (p-value 0.000). People living in urban area had higher use of appropriate antibiotics; 70 (67.3%) versus 101 (55.7%) in inappropriate group with p-value 0.05. Patients having high school or more-higher education had higher frequency of appropriate use of antibiotics; 73 (70.8%) versus 97 (55.2%) in inappropriate group, p-value 0.01. On average there was poor knowledge of people regarding AMR, on 37 (35.6%) patients in appropriate and 39 (22.2%) in inappropriate antibiotics group had knowledge regarding antibiotics, p-value 0.01. Conclusion: Age <40 years, living in rural area, and low level of education are significant factors of inappropriate antibiotics use. The knowledge of AMR was poor in all people, however, people having appropriate use of antibiotics had higher knowledge of AMR. Keywords: Antimicrobials, antibiotics, inappropriate use,